Detecting cancer metastasis and accompanying protein biomarkers at single cell levels using a 3D-printed microfluidic immunoarray - Sharafeldin, Mohamed; Chen, Tianqi; Ozkaya, Gulsum Ucak; Choudhary, Dharamainder; Molinolo, Alfredo A.; Gutkind, J. Silvio; Rusling, James F. (ELSEVIER ADVANCED TECHNOLOGY, 2021)
A low-cost microfluidic microarray capable of lysing cells and quantifying proteins released after lysis was designed and 3D-printed. The array lyses cells on-chip in lysis buffer augmented with a 2s pulse of a sonic cell disruptor. Detection of desmoglein 3 (DSG3), a metastatic biomarker for head and neck squamous cell carcinoma (HNSCC), along with two accompanying HNSCC biomarkers from a single cell lysate of oral cancer cell cultures was demonstrated. A lysis chamber and reagent compartments deliver sample and reagents into detection chambers decorated with capture antibodies immobilized onto inner walls coated with a highly swollen 3D chitosan hydrogel film. Sandwich immunoassays are achieved when captured analytes labeled with biotinylated secondary antibodies, which then capture streptavidin-poly [horse radish peroxidase] (Poly-HRP). Subsequent delivery of super-bright femto-luminol with H2O2 generates chemiluminescence captured with a CCD camera. DSG3 is membrane-bound protein in HNSCC cells of invaded lymph nodes, vascular endothelial growth factor-A (VEGF-A), vascular endothelial growth factor-C (VEGF-C) were positive controls overexpressed into the HNSCC culture medium. Beta-tubulin (beta-Tub) was used as a loading control to estimate the number of cells in analyzed samples. Limits of detection (LOD) were 0.10 fg/mL for DSG3, and 0.20 fg/mL for VEGF-A, VEGF-C and beta-Tub. Three orders of magnitude semilogarithmic dynamic ranges were achieved. VEGF-A showed high in-cell expression, but VEGF-C had low levels inside cells. The very low LODs enabled quantifying these proteins released from single cells. Strong correlation between results from on-chip cell lysis, conventional off-line lysis and ELISA confirmed accuracy.
Keywords: Chemiluminescence; Microfluidics; HNSCC; Metastatic cancer biomarkers; Single cell; 3D printing; LYMPH-NODE METASTASES; ULTRASENSITIVE MULTIPLEXED DETECTION; HYBRIDIZATION CHAIN-REACTION; NECK-CANCER; SQUAMOUS CARCINOMA; HEAD; SENSITIVITY; EXPRESSION; PATTERNS; DEVICES; Biophysics; Biotechnology & Applied Microbiology; Chemistry; Electrochemistry; Science & Technology - Other Topics